2014
DOI: 10.1353/rhe.2014.0032
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hispanic-Serving Institutions (HSIs), Emerging HSIs, and Non-HSIs on Latina/o Academic Self-Concept

Abstract: Latina/os are now the largest minority group at four-year colleges and universities (Fry, 2011). As Latina/o enrollments in higher education have steadily increased over previous decades, a significant proportion of these students enroll at a unique institutional type, Hispanic-Serving Institutions (HSIs). Only 8% of all postsecondary institutions are designated as HSIs, yet they enroll approximately 54% of all Latina/o college students (Contreras, Malcom, & Bensimon, 2008;Santiago, 2008). In fall 2008, among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 38 publications
1
59
0
Order By: Relevance
“…Echoing the sentiments of other participants, one student emphasized the benefits resulting from "the cultural change that will occur with a demographic change of students." This aligns with the organizational culture literature that has examined the resulting benefits at HSIs to educational outcomes (e.g., Cuellar, 2014;Doran, 2015). These insights from participants address environment, mission, and socialization components of organizational culture as articulated by Tierney (1988), highlighting how the ongoing demographic changes at an HSRI would, in fact, allow a research institution to "flourish" and more fully address its mission.…”
Section: Engaging the Benefits Of An Hsrisupporting
confidence: 68%
See 1 more Smart Citation
“…Echoing the sentiments of other participants, one student emphasized the benefits resulting from "the cultural change that will occur with a demographic change of students." This aligns with the organizational culture literature that has examined the resulting benefits at HSIs to educational outcomes (e.g., Cuellar, 2014;Doran, 2015). These insights from participants address environment, mission, and socialization components of organizational culture as articulated by Tierney (1988), highlighting how the ongoing demographic changes at an HSRI would, in fact, allow a research institution to "flourish" and more fully address its mission.…”
Section: Engaging the Benefits Of An Hsrisupporting
confidence: 68%
“…Although few studies on HSIs use organizational theory, "empirical research suggests that the organizational culture of each HSI is unique and enhances a number of important outcomes" (García, 2015, p. 89). For example, Cuellar (2014) studies the impact of the institutional contexts of HSIs, Emerging HSIs, and non-HSIs on the academic self-concept of Latino/a students. Doran's (2015) case study of the University of Texas at San Antonio focuses on an HSI with Tier One aspirations and the impact of this "striving" on its historical focus on access.…”
Section: Conceptual Framework: Organizational Culture Literature and mentioning
confidence: 99%
“…Similarly, González (2008) contends that Latinx students at HSIs engage in civic activities at similar rates as white students, despite the fact that numerous studies have shown that People of Color 3 are less likely to be civically engaged. Cuellar (2014) found that Latinx students at HSIs show a significant increase in their academic self-concept over four years.…”
Section: Literature Reviewmentioning
confidence: 94%
“…HSIs can assist students in developing their academic skills and self-concepts, (Robbins et al, 2004). HSIs have shown a positive influence on first year Latinx students' higher-order learning (Fosnacht & Nailos, 2015) as well as academic self-concepts despite entering college with significantly lower self-concepts than their peers at non-HSIs (Cuellar, 2014). As such, future research should continue to examine how HSIs advance Latinx academic skills and self-perceptions given the strong interrelationship with student success.…”
Section: Outcomes Of Empowermentmentioning
confidence: 98%
“…Latinx students attending two-year HSIs are more likely to have entered with AP credit in high school and a desire to transfer , while those attending fouryear HSIs are more likely to have lower standardized high school math scores (Núñez & Bowers, 2011). Further, Latinx students enter four-year HSIs with lower self-perceptions of their academic abilities as compared to their peers attending non-HSIs (Cuellar, 2014). These studies collectively demonstrate the tremendous potential for HSIs to develop the academic talents of Latinx students (Núñez & Bowers, 2011).…”
Section: Inputsmentioning
confidence: 99%